The Influence of Religious Activities on Learning Achievement in Aqidah-Akhlak among Students of Madrasah Tsanawiyah Tahfizhul Qur’an Al-Fatah Sambi - Abdurrahman, Ahmad Faiz; Sukari, Sukari; Sugiyat, Sugiyat (MANAZHIM, 2026)
This study is motivated by the limited empirical research examining the relationship between religious activities and learning achievement in the subject of Aqidah-Akhlak, particularly within tahfizh madrasah settings, even though this context has important implications for character formation and the effectiveness of religious education. The study aims to analyze students’ level of engagement in religious activities, measure their learning achievement in Aqidah-Akhlak, and examine the extent to which religious activity influences that achievement. A quantitative correlational survey design was employed, involving a sample of 62 students from MTs Tahfizhul Qur’an Al-Fatah Sambi selected through stratified proportional random sampling. Data were collected using a 20-item Likert-scale questionnaire measuring religious activity and documentation of school report grades for learning achievement, and were analyzed using descriptive statistics and simple linear regression in SPSS. The results indicate that both religious-activity levels and Aqidah-Akhlak learning achievement fall into the “medium” category, with mean scores of 65.94 and 84.69, respectively. Inferential analysis reveals a positive and statistically significant effect of religious activity on learning achievement (B = 0.131; p = 0.032), although the contribution of religious activity to variance in achievement is relatively small (R = 0.229; R² ≈ 0.052, or ≈ 5.2%). These findings are consistent with character-education theory, which emphasizes habitual religious practice as a driver of motivation and discipline, while simultaneously underscoring the need for multivariate models to more comprehensively explain academic outcomes. The study implies the importance of strengthening structured religious habituation integrated with instructional strategies and recommends future research using longitudinal, multi-site, and mixed-methods designs to explore mediating mechanisms and additional control variables.